Drivers’ Information and Practical Training Assessment Results Management System: A Recommendation for NIT - Mahuwi, Deogratias Tasilo; Ntyangiri, Christopher Denis; Mwansasu, Isaya Mathew; Kamugisha, Lydia Thomas (ABUAD Journal of Engineering Research and Development (AJERD), 2025)
Road Traffic Injuries (RTIs) resulted from Road Traffic Accidents (RTAs) have high contribution to human deaths globally where in 2023, 1733 RTAs which resulted into 1647 deaths were recorded in Tanzania with human factor contributing 97% of the RTAs. The situation has raised a need to conduct a study to identify how drivers training processes are handled in Tanzania. The National Institute of Transport (NIT) was selected for the study to present the current situation since it is the institute offering training to the professional drivers and drivers’ instructors in Tanzania. In-car, Automated, Simulator-based, Structured Off-Road and Clinical Drivers’ Assessments were identified in the literature as the common methods for assessing the drivers’ practical skills. Interview was used to collect data from the targeted personnel who were identified as Director of Academics Support Services (DASS), Head of Department (HoD) for driving courses and National Institute of Transport Certified Driver Instructors (NIT-CDIs). The research findings highlighted issues in the process of drivers’ registration, record keeping and backup, assessment methods, result verification, analysis and reporting. The study has recommended algorithms in some crucial aspects of the drivers’ trainings that could be used to improve the standard of the drivers’ training processes which could ultimately contribute to the reduction of RTAs and RTIs in Tanzania and globally. Further researches are needed to study the driver training processes in other institutes in Tanzania and recommend better, affordable and more effective approaches for handling drivers’ trainings.